Mud key [videorecording (DVD)] - Sohn, Coley; Sohn, Coley; Bagley, Linda; McClarnon, Chad; MacKenzie, Chris, (Actor); Sullivan, Quinn (Freestyle Digital Media, 2024)
A lefty lesbian couple and their lapdog accidentally beach their boat on a tiny remote Florida Key, crashing a right wing couple's campsite, and all must wait for the tide to come back in for them to get out.